Demographic Profiles of Prolapse Lumbar Intervertebral Disc (PLID) Patients attended at a Tertiary Care Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Prolapse lumbar intervertebral disc (PLID) can occur in different age and gender patients. Objective: The purpose of the present study was to observe the demographic profiles of prolapse lumbar intervertebral disc (PLID) patients.Methodology: This cross-sectional study was carried out in the department of Neurosurgery at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from March 2006 to October 2007 for a period of one and half year. Prolapse lumbar intervertebral disc (PLID) patients who were admitted in the Department Neurosurgery at BSMMU, Dhaka, Bangladesh after clinical and radiological evaluation were selected as study population. Age, sex, occupations of the patients were recorded.Results: A total number of 59 PLID patients were recruited of this study. Among them 54 cases were male and the rest 5 cases were female patients. The mean age of the patients was 40.8±11.9 years and the lowest and highest ages were 21 and 65 years respectively. The male to female ratio was 11:1. Nearly 55.0% cases of the patients engaged with manual work and the rest 45.8% cases were non-manual worker.Conclusion: In conclusion young adult male patients engaged in manual works are the most commonly suffering from PLID.Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):83-86